2019
DOI: 10.1016/j.labeco.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Emigrant selection and wages: The case of Poland

Abstract: In this paper, I use a unique individual-level pre-migration labour market dataset for Poland to examine emigrant selection in two major destination countries, the United Kingdom and Germany. I compare the pre-migration observable and unobservable characteristics of emigrants with those of non-emigrants in Poland. First, I find that Polish emigrants to the UK are more similarly educated to non-emigrants while being more negatively selected on residual wages. Second, emigrants to Germany are disproportionately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(76 reference statements)
2
7
0
Order By: Relevance
“…This enabled us to show that a large share of the selectivity occurs even before individuals are fully able to display their labour market abilities, suggesting that previous studies have underestimated emigrants’ selectivity levels across developed countries. Second, we established clear differences in the selectivity pattern across destination regions, in line with recent studies that have reached similar conclusions (Borjas et al, 2019 ; Parey et al, 2017 ; Rosso, 2019 ). Finally, our empirical findings regarding the gender-based differences in selectivity levels call for a more in-depth examination of the impacts of gender and family status on emigrants’ selectivity levels.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This enabled us to show that a large share of the selectivity occurs even before individuals are fully able to display their labour market abilities, suggesting that previous studies have underestimated emigrants’ selectivity levels across developed countries. Second, we established clear differences in the selectivity pattern across destination regions, in line with recent studies that have reached similar conclusions (Borjas et al, 2019 ; Parey et al, 2017 ; Rosso, 2019 ). Finally, our empirical findings regarding the gender-based differences in selectivity levels call for a more in-depth examination of the impacts of gender and family status on emigrants’ selectivity levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, other studies have found intermediate selection, showing that emigrants are drawn from the middle of the wage distribution, as in the case of emigrants from Mexico and Israel to the US (Chiquiar & Hanson, 2005 ; Gould & Moav, 2016 ), while others found negative patterns of self-selection among emigrants (Moraga, 2011 ). Such mixed results confirm the model’s expectation that self-selection patterns are sensitive to the specific source and destination countries under observation (Dustmann & Görlach, 2015 ; Parey et al, 2017 ; Rosso, 2019 ). 4 However, even when using the same source and destination countries, as in the case of Mexican emigrants to the US, findings are inconsistent for patterns of self-selection (Chiquiar & Hanson, 2005 ; Kaestner & Malamud, 2014 ; Moraga, 2011 ).…”
Section: Theory and Previous Studiessupporting
confidence: 75%
See 2 more Smart Citations
“…As far as migrant selection is concerned, migrants tend to move to countries where their skills are relatively scarce, filling in gaps in the natives' set of skills (Aparicio-Fenoll and Kuehn, 2019). Migrants' selection on observable and on unobservable characteristics, however, do not necessarily move in the same direction and are responsive to migration regimes in destination countries (Rosso, 2019). Policies that select migrants based on education level (pointbased systems) do not necessarily attract the immigrants with the most sought-after skills and those that will be the most highly rewarded in the host country labour market (Bertoli and Stillman, 2020).…”
Section: What Did We Learn? a Few Lessons For Migration Policymentioning
confidence: 99%